FROM THE HISTORY OF VISITS BY BRITISH DIPLOMATS TO GEORGIA - Otar Nikoleishvili (Scientific Research and Experimental Development, 2024)
Georgia, because of its strategic location and importance, have always been under the special interests of the foreign visitors. One of those persons was a British diplomat and traveler Augustus Henry Mounsey (1834–1882). During his career, Augustus Henry Mounsey served as a diplomat in Portugal, Germany, Austria, and Japan. He visited our country in the winter of 1865-1866. He described impressions of this journey in his book “A Journey Through the Caucasus and the Interior of Persia, which was published in London in 1872. Besides this, that he traveled around almost whole Georgia, he did not give us the detailed information about cities and regions of our country. As it known, Augustus Henry Mounsey’s above-mentioned book is not widely studied for the researchers of the history of Georgia. That is why, we can say, that the author’s description and opinions are very valuable for the study of the history of that period of our country